Towards a New Bridge Live Load Model for South Africa. Issue 2 (3rd April 2019) - van der Spuy, Pierre; Lenner, Roman
ABSTRACT: South Africa's bridge design code, TMH7, was first introduced in 1981. In deriving the code a fully probabilistic approach was not possible due to insufficient data at the time. Various studies have shown that the code underestimates measured values in hogging, sagging and shear. A new load model, based on seven years of Weigh in Motion (WIM) data, is developed in this contribution. The Weibull distribution offers the best solution to the statistical extrapolation of load effects. A return period of 975 years is used to obtain static characteristic values for the required internal forces. As a result, the most appropriate load model for South African traffic consists of either tridem or quad axle group with an extrapolated axle weight of 160 kN and an appropriate constant UDL loading as specified in this paper. It is shown that TMH7 NA loading produces significantly smaller values than the measured WIM data for all load effects. This serves as motivation to urgently revise TMH7 loading.